ANALISIS KINERJA PEGAWAI BADAN KEPEGAWAIAN DAERAH KABUPATEN WONOGIRI DITINJAU DARI KOMUNIKASI, KOMPETENSI DAN LINGKUNGAN KERJA - Yeni Trihastuti; Bambang Mursito; Eny Kustiyah (JURNAL ILMIAH EDUNOMIKA, 2020)
The aim of this research are to find out the influences both simultaneously and partially of communication, competence, and work environment on the employee performance of the Wonogiri Regency Regional Personnel Agency. The population in this study were all employees at the Wonogiri Regency Regional Personnel Agency, which numbered 54 employees. The samples in this study were 54 respondents. Data collection techniques in this research were using observation, documentation, questionnaires, interview and literature study. Technical data analysis in this research were using classic assumption test, multiple linier test, t test, lf test, the coefficients determined. The result of this study: There is a simultaneous and partially influence of communication, competence, land work environment on the employee performance of the Wonogiri Regency Regional Personnel Agency. Keylwords : communication, lcompetence, lworklenvironment, lemployeelperformance.